THE EFFECT OF VIRGIN COCONUT OIL WASTE IN THE DIET OF BROILER CHICKEN ON THE MICROSTRUCTURAL OF MUSCLE AND DIGESTIVE ORGANS - Dina Oktaviana (SANGKAREANG, 2016)
The experiment was conducted to examine the effect of Virgin Coconut Oil (VCO) microstructural of digestive organs of broiler. One hundred and twenty five of broiler were divided into 5 treatments such as R-O (basal diet), R-0.5 (0.5% VCO waste), R-1.0 (1.0% VCO waste), R-1.5 (1.5% VCO waste) and R-2.0 (2.0% VCO waste). Each treatments consisted of 5 replication with 5 head experiment the birds. The birds were raised for 5 weeks. The data was analyzed by using Completely Randomized Design (CRD) with one way analysis. The difference among treatments were tested using Duncan’s new Multiple Range Test (DMRT). The statistical analysis result showed that the addition of VCO waste at level of 2.0 % did not affect muscle tissue, but influenced the changes of tissues of liver, kidney and proventiculus.